2020
DOI: 10.1111/1462-2920.15324
|View full text |Cite
|
Sign up to set email alerts
|

A unique porin meditates iron‐selective transport through cyanobacterial outer membranes

Abstract: Summary Cyanobacteria are globally important primary producers and nitrogen fixers with high iron demands. Low ambient dissolved iron concentrations in many aquatic environments mean that these organisms must maintain sufficient and selective transport of iron into the cell. However, the nature of iron transport pathways through the cyanobacterial outer membrane remains obscure. Here we present multiple lines of experimental evidence that collectively support the existence of a novel class of substrate‐selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 71 publications
3
31
2
Order By: Relevance
“…On the other hand, cells transformed with pDC1841K showed no sign of complete chromosome segregation even after several rounds of streaking onto BG11 plates with increasing antibiotic concentration (Figure 2B). Our results are in agreement with the work of Qiu et al [19], in which the authors report to have failed in generating a full knockout mutant of gene slr1841. This suggests that Slr1841 likely plays an essential role in Synechocystis under the tested conditions, possibly involved in the uptake of micronutrients and/or in stabilizing the OM.…”
Section: Slr1841 Encodes An Essential Protein While the Remaining Slh/oprb-domain Containing Outer Membrane Proteins Are Not Essential Fosupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, cells transformed with pDC1841K showed no sign of complete chromosome segregation even after several rounds of streaking onto BG11 plates with increasing antibiotic concentration (Figure 2B). Our results are in agreement with the work of Qiu et al [19], in which the authors report to have failed in generating a full knockout mutant of gene slr1841. This suggests that Slr1841 likely plays an essential role in Synechocystis under the tested conditions, possibly involved in the uptake of micronutrients and/or in stabilizing the OM.…”
Section: Slr1841 Encodes An Essential Protein While the Remaining Slh/oprb-domain Containing Outer Membrane Proteins Are Not Essential Fosupporting
confidence: 93%
“…Growth phenotype characterization under photoautotrophic conditions in liquid medium indicated that none of the disrupted genes encode essential proteins for Synechocystis, at least under standard growth conditions, as all mutant strains showed similar growth rates as compared to that of the wild-type strain (Supplementary Material Figure S1). Qiu et al were also capable of generating full knockout mutants of genes sll1271, sll0772, slr0042 and sll1550, but not of slr1908 [19]. This discrepancy could be related to differences in Synechocystis sp.…”
Section: Slr1841 Encodes An Essential Protein While the Remaining Slh/oprb-domain Containing Outer Membrane Proteins Are Not Essential Fomentioning
confidence: 99%
See 1 more Smart Citation
“…3), we suggest that low‐fl Synechocystis 6803 cells lose their ability to recover after iron has been reintroduced into the medium. Studies have shown that the expression of iron uptake genes is upregulated under Fe‐limiting conditions (Singh et al ., 2003; Hernández‐Prieto et al ., 2012; Qiu et al ., 2018; Qiu et al ., 2021) and Fe transport rates in Synechocystis 6803 can increase by as much as 40‐fold compared with uptake rates in non‐limited cells (Kranzler et al ., 2011). This means that when iron bioavailability suddenly increases, high cellular uptake rates result in a surge of internal Fe quotas.…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was described that in Synechocystis sp. the porin Slr1908 mediates the transport of inorganic iron [25]. Slr1908-like sequences were identified in many cyanobacterial species, indicating a porin-dependent iron uptake in cyanobacteria Nine porin-like genes were assigned based on sequence alignments and amino acid sequence properties in the genome of Anabaena sp.…”
Section: Introductionmentioning
confidence: 99%